PERAN DA'I DALAM MENINGKATKAN MINAT IBADAH SHOLAT FARDHU MASYARAKAT DI KECAMATAN DOLOK KABUPATEN PADANG LAWAS UTARA - ISMAIL NASUTION (Department of Islamic Communication and Broadcasting - Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Apart from the rewards of prayer, it amazes and amazes us, because there is so much calm in our lives. It turns out that Allah has entrusted us with so many secrets, one of which is health and healing. Although the main purpose of prayer to uphold devotion to Allah . However, it is a shame that in Dolok District there are still many who squander this enjoyment. There are still many who abandon prayer. Even though the average person in Dolok District knows the benefits of offering fardhu prayers. The word da'i comes from Arabic which means someone who invites. The term communication science is called a communicator. In Indonesia, preachers are also known by other names such as mubaligh, ustadz. This is based on their existence duties being the same as those of preachers. In a special sense, a da'i is a person who invites other people, either directly or indirectly, with words, actions or behavior towards good or better conditions according to the laws of the Qur'an and Sunnah. Da'i strategies in Coaching congregational prayers is how to ensure that preachers can utilize the right time and place to invite people to join in congregational prayers. In this case, the dai uses verbal da'wah and also bil hal da'wah. Where oral da'wah utilizes community activities to convey the importance of attending congregational prayers, such as Friday sermons, recitations ta'lim assembly, and also other community religious activities such as halal bi halal or commemoration of the Prophet's birthday.